1996
DOI: 10.1128/iai.64.6.2041-2046.1996
|View full text |Cite
|
Sign up to set email alerts
|

Inability of the Francisella tularensis lipopolysaccharide to mimic or to antagonize the induction of cell activation by endotoxins

Abstract: We studied the ability of the lipopolysaccharide (LPS) extracted from a vaccine strain of Francisella tularensis (LPS-Ft) to mimic LPSs from other gram-negative bacteria for activation of various murine cell types or to antagonize the effects of other LPSs. We found that activation of macrophages for the production of tumor necrosis factor alpha and NO, of pre-B lymphocytes for the expression of surface immunoglobulins, and of bone marrow cells for the expression of LPS-binding sites was either undetectable wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…It was important to determine whether the LPS of F. tularensis might act antagonistically to E. coli LPS. The rationale was the previous finding that F. tularensis LPS is a very weak activator of macrophage cytokine secretion (Sandström et al, 1992;Ancuta et al, 1996). The previous studies did not rule out the possibility that F. tularensis LPS is capable of binding to TLR4 without exerting an agonistic effect.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It was important to determine whether the LPS of F. tularensis might act antagonistically to E. coli LPS. The rationale was the previous finding that F. tularensis LPS is a very weak activator of macrophage cytokine secretion (Sandström et al, 1992;Ancuta et al, 1996). The previous studies did not rule out the possibility that F. tularensis LPS is capable of binding to TLR4 without exerting an agonistic effect.…”
Section: Discussionmentioning
confidence: 54%
“…After washing (0 h), all values were below the lower limit of detection, <15 pg ml -1 for TNF-a and <7.5 pg ml -1 for IL-1 b. E. coli LPS (5 mg ml -1 ) was about the same (P > 0.10), irrespective of addition of F. tularensis LPS (5 mg ml -1 ), and F. tularensis LPS alone induced a barely detectable secretion of TNF-a (Table 5). This confirms previous data indicating that F. tularensis LPS is a much weaker inducer of TNF-a than E. coli LPS (Sandström et al, 1992;Ancuta et al, 1996) and showed that it did not function as an antagonist to E. coli LPS.…”
Section: Inability Of F Tularensis-derived Lps To Inhibit the Cytokimentioning
confidence: 99%
“…During entry, LVS prevents NADPH oxidase assembly at the phagosome and thereby evades early elimination by toxic ROS. Thereafter, LVS escapes the phagosome and enters the PMN cytosol, where it survives for at least 12 h. In this context, PMN may sustain infection by disseminating bacteria to distal sites without inducing a significant inflammatory response (a notion consistent with the low bioactivity of Francisella endotoxin [26,27]). Alternatively, infected PMN may be ingested by macrophages and in this manner, propagate infection as has been reported recently for Leishmania [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ft-LPS is composed of an unusual lipid A that lacks most of the chemical groups required for interaction with TLR4. 75,76 In a mouse model, B1a B cells play an important role in limiting intraperitoneal infection by producing anti-LPS antibodies at early times of infection. 77 F. tularensis can infect a wide range of cells without being detected.…”
Section: Francisella Tularensismentioning
confidence: 99%